Structural analysis of the Polish Code of Medical Ethics - Anna Augustynowicz; Adam Skowron; Michał Waszkiewicz; Konrad Zygarski; Janusz Sytnik-Czetwertyński (Kazimierz Wielki University, 2019)
In this article is described the structural analysis of the Polish Code of Medical Ethics. It is presented in the context of the Constitution of the Republic of Poland; it is also analysed the scope of the Code of Medical Ethics.